STUDY OF DEGRADATION PROCESSES OF PEROVSKITE SOLAR CELLS - Azimov J.T., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The degradation processes of perovskite solar cells with a p-i-n structure based on PEDOT: PSS were studied, and their current-voltage characteristics were measured. It is shown that the general form of the current-voltage characteristic weakly depends or does not depend on the voltage scanning direction. The most significant changes in characteristics and a significant decrease in Isc and Voc are observed 12 days after sample production, and the magnitude of the decrease in performance characteristics depends on the conditions of preparation of the absorber.